Pekarangan Produktif untuk Pemenuhan Kebutuhan dan Ketahanan Pangan Kota Jakarta - Rendy Primrizqi (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
With a population of more than 10 million people, DKI Jakarta has a challenge to meet their food needs. The lack of food production in the city makes DKI Jakarta dependent on other regions for food. There is an urgent need of alternative solution to help DKI Jakarta meet its food needs. The implementation of urban farming is seen as an alternative to tackle this challenge. By conducting urban farming, food production is not limited to locations that are regulated in regulations so that the use of private land become possible. Considering that 48.41% of DKI Jakarta is a residential area, this area holds a great potential to optimize urban farming practice, especially if there is an optimal utilization of the house yard. In addition, stakeholder engagement is essential for a more effective, massive, and sustainable practice of urban farming. The optimal collaboration among Penta Helix stakeholders becomes the main goal. As DKI Jakarta is a dense city, solutions are needed to conduct urban farming in narrow areas. It is hoped that innovative architectural interventions can replace the role of the house yard as a media of conducting urban farming. This research/article also encourages further writing and/or research related to the issue of meeting food needs and increasing food security in DKI Jakarta, especially related to optimizing stakeholder engagement and more comprehensive and detailed architectural interventions to facilitate implementation in the field.